Development and Implementation of Mobile Application for Warehouse Inventory Reporting System - Julian Ega Prabowo; Sela, Enny Itje (Journal of Informatics and Communication Technology (JICT), 2024)
The company is engaged in the sale of emping mlinjo crackers and currently still uses manual recording methods to manage its operational activities. The main problem faced is the process of making monthly reports to record the movement of goods in and out of goods and monitor the stock of finished goods and raw materials. Along with the rapid growth of the company, this manual method has become inefficient in handling the high volume of goods and many daily transactions. This often leads to errors and discrepancies in reports, resulting in less efficient distribution of goods. This research aims to digitize the warehouse management system of warehouse management by developing a reporting application for the emping warehouse. goods. This application is designed to monitor the movement of goods and generate reports digitally. It is expected that this application will improve operational efficiency by facilitating data recording and management by the SO (Sales Order) Team, Sales Order Team, Production Team, Distribution Team, and provide convenience for the owner as a super admin in managing warehouse activities. The research method used is interviews and observations to identify the problems faced by the company. Based on the findings, the design, development, and implementation of the application and system testing were carried out. Descriptive analysis was used to evaluate the impact of the application on warehouse management and company operations. The results showed that the application was effective in recapitulating incoming and outgoing goods, making it easier to generate reports, and calculating profit or loss from sales transactions. The app enables real-time monitoring, simplifies data input by employees, and increases transaction audit transparency. The digital reporting system simplifies warehouse management, improves operational efficiency, and reduces recording errors and stock management mistakes.